Cryogenic air supply for cooling built-in-place refuge alternatives in hot mines (MME Technical-Paper Abstracts) - Lincan Yan; David Yantek; Miguel Reyes; Bruce Whisner; Joseph Bickson; Justin Srednicki; Nicholas Damiano; Eric Bauer (Society for Mining, Metallurgy & Exploration)
Built-in-place (BIP) refuge alternatives (RAs) are designed to provide a secure space for miners who cannot escape during a mine emergency. Heat and humidity buildup within RAs may expose miners to physiological hazards such as heat stress. To minimize the risk of heat stress, Title 30 Code of Federal Regulations (CFR), or 30 CFR, mandates a maximum allowable apparent temperature (AT) for an occupied RA of 35 °C (95 °F). The National Institute for Occupational Safety and Health (NIOSH) has conducted extensive research on the thermal environment of occupied RAs intended for use in underground coal mines. NIOSH research has demonstrated that a fully occupied BIP RA can exceed the AT limit by more than 5.6 °C (10 °F) in mines with elevated mine strata and air temperatures. In this circumstance, an RA cooling system could provide a solution. This paper provides an overview of test methodology and findings as well as guidance on improving the performance of a cryogenic air system prototype by optimizing the flow rate, increasing the tank storage capacity, and improving the efficiency of the heat exchanger of the cryogenic system. This may enable BIP RAs to meet the 35 °C (95 °F) AT limit in mines with elevated temperatures. The information in this paper is useful for RA manufacturers and mines that may choose to implement a cryogenic air system as a heat mitigation strategy.